2013
DOI: 10.1111/j.1477-2574.2012.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor level of agreement on the management of postoperative pancreatic fistula: results of an international survey

Abstract: This survey discloses important disagreements worldwide regarding the management of POPF after both Whipple surgery and DP. The standardized management of POPF would better facilitate the comparison of outcomes in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
1
25
0
9
Order By: Relevance
“…A randomized trial has shown that continuous enteral nutrition improved the rate of and/or the interval to closure of pancreatic AL [40]. Re-alimentation is only possible when the infectious syndrome has been well controlled [35] and when the AL output is low (less than 50 ml/day). Somatostatin ® or its analogues can be used when the output is high (> 100 or 200 ml/day), because they decrease the output and/or shorten the course of these AL [39][40][41][42].…”
Section: Medical Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…A randomized trial has shown that continuous enteral nutrition improved the rate of and/or the interval to closure of pancreatic AL [40]. Re-alimentation is only possible when the infectious syndrome has been well controlled [35] and when the AL output is low (less than 50 ml/day). Somatostatin ® or its analogues can be used when the output is high (> 100 or 200 ml/day), because they decrease the output and/or shorten the course of these AL [39][40][41][42].…”
Section: Medical Treatmentmentioning
confidence: 96%
“…For pancreatic AL, except when the patient is asymptomatic, the question is whether to stop oral feeding in order to decrease exocrine secretion [35], notably in the patient with pancreatico-gastrostomy [39]. Associated nutritional support (total parenteral nutrition or eventually continuous enteral nutrition by nasojejunal drip via a tube placed in the efferent loop of the gastrojejunostomy) is recommended.…”
Section: Medical Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent advances in operative techniques and perioperative care have resulted in lower morbidity and mortality rates; however, POPFs may still lead to intra-abdominal abscess, hemorrhage, and sepsis. Although the early diagnosis and prevention of POPF have been extensively discussed, the management of patients after distal pancreatectomy remains unclear [2]. …”
Section: Introductionmentioning
confidence: 99%
“…The preceding data in this chapter underscore the wide variety of strategies that have been employed to prevent pancreatic exocrine complications after distal pancreatectomy and the very limited success that any single strategy has enjoyed. Indeed, a recent survey of hepatopancreatobiliary surgeons worldwide demonstrated that there is little consensus on the management of patients with POPF [40].…”
Section: Management Of Complications Of Pancreatic Leakmentioning
confidence: 99%